Penerapan Kurikulum Merdeka dalam Pengimplementasian Pendidikan yang Sesuai dengan Kodrat Alam dan Zaman - Irianti, Refsa Ina (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2024)
Education is a conscious and planned effort in realizing learning. Education is classified into three parts, namely the narrow meaning of education, the broad meaning of education and the alternative meaning of education. However, education changes with the times. The research method used in this study is the literature research method. The data collection technique taken by this study is a technique that collects and reviews from existing journals or research, both national and international research. Regarding the data analysis technique, the researcher took a qualitative descriptive analysis technique. Based on the research, it can be concluded that the independent curriculum is a form of implementing education that is in accordance with the nature and nature of the times that was initiated by Ki Hajar Dewantara.